Experimental Investigation of the Effect of Feed Rate and Negative Tool Rake Angle in High Speed Hard Turning - Al Hazza, Muataz Hazza Faizi; Adesta, Erry Yulian Triblas (Design for Scientific Renaissance, 2013)
The aim of this paper is to study experimentally the influence of feed rate and negative tool rake angle on surface roughness and flank wear length during high speed hard turning. AISI 4340 was used as work piece material. This steel is hardened to 60 HRC, machined by a mixed ceramic tool (Al₂O₃- TiC). The experiment was obtained with constant cutting depth (0.15 mm), constant cutting speed (325 m/min), four different feed rates (0.075 – 0.15 mm/rev) and three different tool rake angles (0o, - 6, -12o). The experimental results showed that roughness has an increasing trend with the increasing of the feed rate. In contrast, the roughness has a decreasing trend as the rake angle increases in the negative direction from (0o) to (-12o). The flanks wear length also affected by the feed rate increasing. Finally in order to identify statistically significant trends in the measured parameters and cutting parameters data i.e. feed rate and rake angle, an analysis of variance (ANOVA) was conducted. By using DOE an optimization solution was obtained